Impacts of Some Meteorological Parameters on Diffuse Solar Radiation Across the Coastal Region of Nigeria - Salifu, S. I.,; Akpootu, D.O,; Kola, T. A,; Nouhou, I.,; Agidi, O. E,; Yusuf, A.,; Aliyu, M. A,; Idris M., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study examines the interplay between meteorological parameters and diffuse solar radiation across various coastal locations. A key finding is the inverse relationship between atmospheric pressure and diffuse solar radiation which implies that higher atmospheric pressure correlates with lower diffuse solar radiation and vice versa. Additionally, mean temperature tends to give a reflection of diffuse solar radiation patterns, suggesting higher diffuse solar radiation with elevated temperatures. Seasonal analysis reveals distinct variations in diffuse solar radiation across locations: Warri experiences its peak (10.6298 MJm-2day-1) in March and a dip in July (8.3896 MJm-2day-1); Benin observes its highest level in April (10.7804 MJm-2day-1) and lowest in December (8.5304 MJm-2day-1); the maximum value for Ikeja was found in March (10.4285 MJm-2day-1) and minimum in December (8.4420 MJm-2day-1) occur during the dry season; and Ogoja records its highest in March (10.9047 MJm-2day-1) and lowest in December (7.8235 MJm-2day-1).This indicates significant seasonal impact on solar radiation in these coastal regions. The highest and lowest monthly averaged mean diffuse solar radiation was recorded in Ogoja and Ikeja respectively.